Pemikiran Islam dan Moderasi dalam Diplomasi: Analisis Audiensi Bersama Masyarakat Malaka-Malaysia - Satiadharmanto, Deddi Fasmadhy; Huda, M Dimyati; Yusuf, Moh Asror (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
This report presents the results of a community service activity conducted in Malacca, Malaysia, with the aim of engaging the local community in a dialogue through the lens of Islamic thought. The discussion focused on the contributions of Prameswara, the King of Palembang, in establishing Malacca as a trade and cultural center in Southeast Asia. Using a participatory approach, the dialogue invited the community to reflect on the Islamic values that shaped Malacca’s history and its pivotal role in social, economic, and cultural interactions. The findings show that historical awareness and understanding of Islamic thought can strengthen the identity of the Malaccan people and encourage collaboration in the preservation of cultural heritage. This report aims to contribute to the development of Islamic and historical studies in the region and promote increased community involvement in safeguarding and enhancing their cultural legacy